Unique, Additive, and Interactive Effects of Types of Intimate Partner Cybervictimization on Depression in Hispanic Emerging Adults - Cantu, Jorge I. (Journal of interpersonal violence, 2022)
The advent of modern technology has inadvertently created newer avenues for intimate partner victimization (IPV) to transpire. This study investigated (a) whether psychological, sexual, and stalking intimate partner cybervictimization (cyber IPV) types were uniquely associated with depression and whether there were (b) additive and (c) interactive effects of cyber IPV types on depression, after controlling for face-to-face IPV among Hispanic emerging adults. Participants were 903 Hispanic emerging adults in the age range of 18 to 29 years (M = 20.68, SD = 2.42; 74% female) attending a public university in South Texas. Participants completed an online questionnaire assessing cyber IPV types (psychological, sexual, and stalking), face-to-face IPV types (physical, psychological, and sexual), and depression. Results indicated that nearly three-fourths (73%) of the sample endorsed at least one type of cyber IPV. Hierarchical regression analysis showed that psychological and sexual cyber IPV was uniquely associated with depression. An accumulating effect (additive effect model) of the three types of cyber IPV on depression was also found. Interaction effect model analysis yielded no significant effects. Findings reveal the detrimental effect of cyber IPV on mental health and calls for institutions and clinicians to develop preventive and treatment programs to aid victim-survivors.